ARumenamides: A novel class of potential antiarrhythmic compounds - Abdelsayed, Mena; Page, Dana; Ruben, Peter C. (Frontiers in Pharmacology, 2022)
Background: Most therapeutics targeting cardiac voltage-gated sodium channels (Nav1.5) attenuate the sodium current (INa) conducted through the pore of the protein. Whereas these drugs may be beneficial for disease states associated with gain-of-function (GoF) in Nav1.5, few attempts have been made to therapeutically treat loss-of-function (LoF) conditions. The primary impediment to designing efficacious therapies for LoF is a tendency for drugs to occlude the Nav1.5 central pore. We hypothesized that molecular candidates with a high affinity for the fenestrations would potentially reduce pore block. Methods and Results: Virtual docking was performed on 21 compounds, selected based on their affinity for the fenestrations in Nav1.5, which included a class of sulfonamides and carboxamides we identify as ARumenamide (AR). Six ARs, AR-051, AR-189, AR-674, AR-802, AR-807 and AR-811, were further docked against Nav1.5 built on NavAb and rNav1.5. Based on the virtual docking results, these particular ARs have a high affinity for Domain III-IV and Domain VI-I fenestrations. Upon functional characterization, a trend was observed in the effects of the six ARs on INa. An inverse correlation was established between the aromaticity of the AR’s functional moieties and compound block. Due to its aromaticity, AR-811 blocked INa the least compared with other aromatic ARs, which also decelerated fast inactivation onset. AR-674, with its aliphatic functional group, significantly suppresses INa and enhances use-dependence in Nav1.5. AR-802 and AR-811, in particular, decelerated fast inactivation kinetics in the most common Brugada Syndrome Type 1 and Long-QT Syndrome Type 3 mutant, E1784K, without affecting peak or persistent INa. Conclusion: Our hypothesis that LoF in Nav1.5 may be therapeutically treated was supported by the discovery of ARs, which appear to preferentially block the fenestrations. ARs with aromatic functional groups as opposed to aliphatic groups efficaciously maintained Nav1.5 availability. We predict that these bulkier side groups may have a higher affinity for the hydrophobic milieu of the fenestrations, remaining there rather than in the central pore of the channel. Future refinements of AR compound structures and additional validation by molecular dynamic simulations and screening against more Brugada variants will further support their potential benefits in treating certain LoF cardiac arrhythmias.